Improvement in overall and cancer‐specific survival in contemporary, metastatic prostate cancer chemotherapy exposed patients. Issue 16 (15th September 2021) - Hoeh, Benedikt; Würnschimmel, Christoph; Flammia, Rocco S.; Horlemann, Benedikt; Sorce, Gabriele; Chierigo, Francesco; Tian, Zhe; Saad, Fred; Graefen, Markus; Gallucci, Michele; Briganti, Alberto; Terrone, Carlo; et al.
Abstract: Introduction: Over the last decade, multiple clinical trials demonstrated improved survival after chemotherapy for metastatic prostate cancer (mPCa). However, real‐world data validating this effect within large‐scale epidemiological data sets are scarce. We addressed this void. Materials and Methods: Men with de novo mPCa were identified and systemic chemotherapy status was ascertained within the Surveillance, Epidemiology, and End Results database (2004–2016). Patients were divided between historical (2004–2013) versus contemporary (2014–2016). Chemotherapy rates were plotted over time. Kaplan–Meier plots and Cox regression models with additional multivariable adjustments addressed overall and cancer‐specific mortality. All tests were repeated in propensity‐matched analyses. Results: Overall, 19, 913 patients had de novo mPCa between 2004 and 2016. Of those, 1838 patients received chemotherapy. Of 1838 chemotherapy‐exposed patients, 903 were historical, whereas 905 were contemporary. Chemotherapy rates increased from 5% to 25% over time. Median overall survival was not reached in contemporary patients versus was 24 months in historical patients (hazard ratio [HR]: 0.55, p < 0.001). After propensity score matching and additional multivariable adjustment (age, prostate‐specific antigen, GGG, cT‐stage, cN‐stage, cM‐stage, and local treatment) a HR of 0.55 ( p < 0.001) was recorded. Analyses were repeated for cancer‐specific mortality after adjustment for other cause mortality in competing risks regression models and recorded virtually the same findings before and after propensity score matching (HR: 0.55, p < 0.001). Conclusions: In mPCa patients, chemotherapy rates increased over time. A concomitant increase in survival was also recorded.